Improving Delivery of Care through Standardized Monitoring in Children with Eosinophilic Esophagitis. Issue 4 (July 2021) - Shukla-Udawatta, Monica; Russo, John; Gunderman, Lauren; Pearlstein, Haley; Wood, Eric; Boyle, Brendan; Erwin, Elizabeth
Abstract : Introduction: Eosinophilic esophagitis (EoE) is a chronic, antigen-driven disorder for which endoscopic monitoring and multidisciplinary care are recommended to achieve histologic remission. The EoE team at our large academic center developed a quality improvement (QI) initiative aimed to reduce variability in monitoring. This QI project focused on completing 3 process metrics within 6 months of diagnosis: (1) outpatient follow-up with a gastroenterologist; (2) referral to an allergist; and (3) Follow-up esophagogastroduodenoscopy (EGD). Methods: In January 2015, our QI team developed a registry of newly diagnosed EoE patients and maintained ongoing, weekly tracking of the process measures. Interventions to increase the completion of the process metrics included educational sessions, proactive reminders to providers, and targeted communications with patient families. Missed opportunities were evaluated by more in-depth chart review and categorized as provider- or patient-driven. Results: We tracked 6-month process metrics from 2015 through 2018. During this interval, follow-up visit rates in GI improved from 77% to 86%, and the percentage of referrals placed to allergy increased from 65% to 77%. The percentage of patients completing a repeat EGD improved from 33% to 61%. Among patients without a repeated EGD, nearly 70% of those missed opportunities were provider-driven. Conclusions: In patients newly diagnosed with EoE, QI interventions, including patient registry development, implementation of a local standard of care, and creating a patient tracking system, improved adherence with national EoE monitoring guidelines.